The Distribution and Source of MRDOs Infection: A Retrospective Study in 8 ICUs, 2013–2019 - Li, Zhan-jie; Wang, Ke-wei; Liu, Bo; Zang, Feng; Zhang, Yu; Zhang, Wei-hong; Zhou, Su-ming; Zhang, Yong-xiang (Infection and drug resistance, 2021)
To analyze the distribution and source of MDROs infection in the ICUs and to provide a basis for formulating more effective prevention and control programs for MDROs. A retrospective investigation was conducted on MDROs infection in 8 ICUs of a large tertiary hospital from July 2013 to June 2019. A total of 2629 strains of MDROs isolated from 1701 inpatients were selected for analysis. The MDROs of the 8 ICUs were divided into two types of four categories according to source: out-of-hospital (out-of-hospital transfer and community acquisition) and in-hospital (in-hospital transfer and department acquisition) infections. CRAB (41.84%) and CRE (35.07%) accounted for the majority of the infecting MDROs. The detection rates of MRSA, CRAB, CRPA and CRE were 61.24%, 83.75%, 43.01% and 30.15%, respectively. The top three infection sites of MDROs were the lower respiratory tract (81.10%), blood (6.70%) and abdominal cavity (5.80%). The out-of-hospital and in-hospital infection rates of MDROs were 50.51% and 49.49%, respectively; the out-of-hospital infection rates for MRSA, CRAB, CRPA and CRE were 43.56%, 55.91, 64.44% and 44.58%, respectively. The proportions of MRSA, CRAB, CRPA and CRE infections contracted in the department were 40.98%, 36.27%, 25.56% and 46.62%, respectively. There was a statistically significant difference between comprehensive ICU and specialized ICU wards as sources for CRAB infections (P < 0.001). The main source of MDROs in the ICU is not the hospital itself entirely. It is particularly important to strengthen the identification of MDRO sources and implement more effective and accurate infection prevention and control measures.